Transport Characteristics of Gallium Nitride Nanowire Field-Effect Transistor (GaN-NWFET) for High Temperature Electronics - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2021)
This paper presents a systematic investigation of high-temperature transport characteristics of a single nanowire Gallium Nitride nanowire field-effect transistor (GaN-NWFET) ranging from room temperature to as high as 350 degrees C for the first time. The GaN-NWFET demonstrated a very good on/off current ratio (Ion/Ioff)of 3 x 10(3) for the p-side and 2:5 - 103 for the n-side at room temperature and considerably well at high temperatures. In fact, the device exhibited an on/off current ratio of 5:5 x 10(2) and a transconductance value of 0:96 mu S for the p-side at 350 degrees C indicating a good gating effect even at high temperatures. Additionally, the device exhibited very high mobilities with the hole mobility of 3:26 - 103 cm(2)/V. s and electron mobility of 3:14 x 10(3) cm(2)/V. s at room temperature. Furthermore, the device showed very high transconductance values of 0:92 mu S and 20:3 mu S at the temperatures of 25 degrees C and 250 degrees C, respectively. As a consequence, the GaN-NWFET devices could find much use not only in high-power, but also in lowpower transistor applications beyond the ambient temperature range (> 300 degrees C) of silicon and silicon-on-insulator technologies for electronic and photonic circuits.
Keywords: GaN-NWFETs; high mobility; high-temperature nanoelectronics; high on/off current ratio; transconductance